Cardiovascular autonomic adaptation to long-term confinement during a 105-day simulated mars mission - Wan, Li (2011)
Introduction: Long-term confinement and microgravity may entail alteration in the regulation of the cardiovascular system. A 105-d pilot study of a Mars mission simulation was conducted to test the cardiovascular response to slow-paced breathing and mental stress. Methods: Finger blood pressure and beat-to-beat heart rate were monitored in six male volunteers taking part in a 105-d Mars mission simulation. Data were collected before, during (Days 35-38, 70-72, and 100), and after confinement. Recordings were performed in the sitting position during 5-min spontaneous breathing, 3-min 12 cycle/min breathing, 3-min 6 cycle/min breathing, and 5-min mental task performance. Results: We found significant U-shaped changes across the confinement period in systolic arterial pressure (SAP), diastolic arterial pressure (DAP), and mean arterial pressure (MAP). In the first month of confinement, mental task performance significantly lowered SAP by 34.23 mmHg and MAP by 19.89 mmHg compared to spontaneous breathing, whereas these changes were reversed during other periods. Furthermore, no differences in arterial pressure and heart rate were found between spontaneous, 12 cycle/min, and 6 cycle/min breathing. Conclusions: Our findings are in line with and extend previous findings on the alteration of blood pressure regulation due to longterm confinement.